2008
DOI: 10.1530/eje-08-0166
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bone mineral density and body proportions between women with complete androgen insensitivity syndrome and women with gonadal dysgenesis

Abstract: Objectives: To compare bone mineral density (BMD) and body proportions between women with complete androgen insensitivity syndrome (CAIS) and with gonadal dysgenesis (GD). Setting: Adult Disorders of Sexual Development and Ovarian Failure Clinics at University College London Hospitals. Design: Retrospective cross-sectional study of three groups of women aged 17-58 years with varying degrees of exposure to sex hormones and different combinations of sex chromosomes. Forty-six subjects had CAIS, 18 had GD and 46,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 27 publications
0
61
0
3
Order By: Relevance
“…Recent data in patients with CAIS and mutations in AR gene, followed from infancy to late adolescence, substantially confirmed such data, showing that mean adult height was closer to median male target height than female target height [10]. Han et al [12] reported that the adult height of women with CAIS and removed gonads at puberty or at older age was significantly higher than those who underwent gonadectomy before puberty (172 vs. 165 cm, respectively). In the same study, the lower to upper body ratio was intermediate between that of females and males [12].…”
Section: Spontaneous Pubertal Pattern In Caismentioning
confidence: 85%
See 1 more Smart Citation
“…Recent data in patients with CAIS and mutations in AR gene, followed from infancy to late adolescence, substantially confirmed such data, showing that mean adult height was closer to median male target height than female target height [10]. Han et al [12] reported that the adult height of women with CAIS and removed gonads at puberty or at older age was significantly higher than those who underwent gonadectomy before puberty (172 vs. 165 cm, respectively). In the same study, the lower to upper body ratio was intermediate between that of females and males [12].…”
Section: Spontaneous Pubertal Pattern In Caismentioning
confidence: 85%
“…Han et al [12] reported that the adult height of women with CAIS and removed gonads at puberty or at older age was significantly higher than those who underwent gonadectomy before puberty (172 vs. 165 cm, respectively). In the same study, the lower to upper body ratio was intermediate between that of females and males [12]. …”
Section: Spontaneous Pubertal Pattern In Caismentioning
confidence: 99%
“…14 Patients in whom gonadectomy is delayed are even taller, suggesting a relative oestrogen defi ciency before gonadectomy. 15 However, no evidence shows that girls with complete androgen insensitivity syndrome start puberty later than girls without the syndrome. 16 The enlarged adult stature in the syndrome is mainly due to the eff ect of the growth-controlling region on the long arm of the Y chromosome, but genome-wide association studies have identifi ed several loci that aff ect adult height.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…15 However, no evidence shows that girls with complete androgen insensitivity syndrome start puberty later than girls without the syndrome. 16 The enlarged adult stature in the syndrome is mainly due to the eff ect of the growth-controlling region on the long arm of the Y chromosome, but genome-wide association studies have identifi ed several loci that aff ect adult height.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…77 No defi nitive evidence shows that bone mineral density is less aff ected in women who had late gonadectomies than in women who had early gonadectomies, although those who had the procedure later in life are substantially taller than those who had early gonadectomies. 78,79 Women with complete androgen insensitivity syndrome do not seem to have an increased risk of fractures. Measurement of bone density at presentation in the case of young women with complete androgen insensitivity syndrome and at 2 yearly inter vals is a useful index of the eff ectiveness of hormone replacement (unpublished).…”
Section: Complete Androgen Insensitivity Syndromementioning
confidence: 99%